Edukasi Dan Simulasi Deteksi Dini Stroke Dengan Pendekatan Fast (Face, Arm, Speech And Time) Posyandu Lansia Dahlia Dusun Tempuran Desa Pelem Kecamatan Pare Kabupaten Kediri - Vela Purnamasari; Tanoto, Wahyu; Muchsin, Enur Nurhayati (STIKES dan AKZI Karya Husada Kediri, 2024)
Stroke is a disease that disrupts the functioning of the brain, if left untreated and not treated properly it can cause further complications and even death. To optimize and minimize the occurrence of stroke, early detection can be done using the approach (Face drooping Arm Weakness Speech difficulty, Time to call doctor/hospital). Comprehensive efforts to manage stroke risk factors in the community must be made. Understanding stroke prevention and detection well is very important. helps in minimizing further complications due to stroke. Health education about early detection of stroke using the FAST method is given to elderly people who have a high risk of stroke. Early detection of stroke using the FAST method (Face drooping Arm Weakness Speech difficulty, Time to call doctor/hospital) could be a solution to increase knowledge of at-risk groups to prevent further complications from stroke attacks. This activity, which was attended by 25 elderly people, went smoothly and enthusiastically. The evaluation results showed that there was a significant increase in good knowledge from 4% to 76% as well as an increase in the ability to detect early stroke using the FAST approach with good results increasing significantly from 0% to 60%. It is hoped that groups at risk of stroke and their families will always maintain a healthy lifestyle and be proactive in participating in Posyandu for the Elderly activities.